PENYELESAIAN SENGKETA ANTAR BADAN ATAU PEJABAT TATA USAHA NEGARA DI PERADILAN TATA USAHA NEGARA - A’an Efendi; Totok Sudaryanto (Kajian Hukum, 2018)
Based on administrative court act, the administrative court is only authorized to hear administrative dispute between individuals or private legal entities against government bodies or official not covering administrative disputes between government bodies or official. Settlement of disputes between agencies or government officials carried out internally with a tierred pattern that ends with the President’s decision. Three reasons for the basis of the idea of providing administrative court competencies to try disputes between government agencies or officials. First, the case law of administrative court in administrative cases between government agencies or officials. Second, the philosophy of the existence of judicial power as in institution to resolve dispute that occur within a state. Third, the right of public to know the process of government management and public decision making, including in the event of a dispute and how to resolve it. This public right is based on the principle of openness and the government works in a public space according to public law. Settlement the disputes in the administrative court with the principle of open trial to the public is a manifestation of the principle of openness. The administrative court of Thailand with the competence to resolve administrative dispute between government agencies or officials can be reference for the reform of Indonesia adminsitative court competencies in the future. Keywords: dispute, government agency or official, administrative court